Evaluation of Durability of Ultra High Performance Fibre Reinforced Concrete (UHPFRC) Through Extreme Temperature - Shelorkar, AP; Chaudhary, VR; Jadhao, PD (International Journal of Computer Sciences and Engineering, 2025)
In the present era of modern concrete technology Ultra High Performance Fibre Reinforced Concrete (UHPFRC) is new cement based material. An inclusion of fibers shows to increases both mechanical and durability properties of UHPFRC. The aim of this study is to determine durability of UHPFRC containing fly ash and Metakaolin. Durability of UHPFRC after exposed to extreme temperature is evaluated. UHPFRC gives better fire resistance. The specimens were exposed to high temperature, specially 200ºC, 400ºC, and 600ºC for 1 hour. The fire resistance of specimen was classified on the basis of their compressive strength and weight loss. Strength loss was not significant at low temperature; up to 200ºC.Metakaolin shows the better performance as compared with fly ash. SEM analysis was also carried out to study effect of extreme temperature on microstructure of UHPFRC.